A molecular risk score integrating BAALC, ERG and WT1 expression levels for risk stratification in acute promyelocytic leukemia - Hecht, Anna; Nowak, Daniel; Nowak, Verena; Hanfstein, Benjamin; Weiß, Christel; Hofmann, Wolf-Karsten; Lengfelder, Eva; Nolte, Florian (Leukemia research, 2015)
To date risk stratification in acute promyelocytic leukemia (APL) is based on highly dynamic leukocyte and platelet counts only. To identify a more robust risk stratification model, a molecular risk score was developed based on expression levels of the genes BAALC, ERG and WT1. Hereby, the main focus was on prediction of relapse. The integrative risk score divided patients into two groups with highly significant differences in outcome. It discriminated a high risk group with a high incidence of relapse successfully from a low risk group with no APL-related events after achievement of first remission. Especially the concurrent presence of molecular risk factors showed to be a negative prognostic factor in APL. The molecular risk score might be a promising approach to guide monitoring of APL patients and therapeutic decisions in the future.